2016
DOI: 10.2135/cropsci2016.03.0183
|View full text |Cite
|
Sign up to set email alerts
|

Pre‐ and Post‐silking Carbohydrate Concentrations in Maize Ear‐leaves and Developing Ears in Response to Nitrogen Availability

Abstract: Maize (Zea mays L.) grain yield is considered to be highly associated with carbohydrate dynamics in leaves and developing ears during the critical period bracketing silking. Carbohydrate changes are sensitive to variation in nitrogen (N) availability, yet a comprehensive analysis of the N effect on various carbohydrate concentrations around silking remains elusive. A 2‐yr field study was conducted to investigate grain yield, N uptake, ear dry matter and carbohydrate concentrations in ear‐leaves and whole ears … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 44 publications
2
16
0
Order By: Relevance
“…To provide context for the NCS and gene expression data, grain yield data are presented in Figure 1 (adapted from [8] and [13]). Briefly, compared to the N0 and N150 treatments, the final grain yield of the N300 treatment was increased by 2.1-4.3 fold in 2010 and by 1.2-2.0 fold in 2011, respectively, and significant differences were detected between N0 and N150 in 2010 ( Figure 1).…”
Section: Dry Matter Accumulation In Developing Ear (Or Kernels) and Fmentioning
confidence: 99%
See 2 more Smart Citations
“…To provide context for the NCS and gene expression data, grain yield data are presented in Figure 1 (adapted from [8] and [13]). Briefly, compared to the N0 and N150 treatments, the final grain yield of the N300 treatment was increased by 2.1-4.3 fold in 2010 and by 1.2-2.0 fold in 2011, respectively, and significant differences were detected between N0 and N150 in 2010 ( Figure 1).…”
Section: Dry Matter Accumulation In Developing Ear (Or Kernels) and Fmentioning
confidence: 99%
“…Over the past decades, numerous studies have been conducted to examine the effects of N supply on leaf growth and photosynthetic capacity [9][10][11][12], leaf carbohydrate concentrations [13][14][15], sucrose loading and transport in the phloem [8], and ear growth and carbohydrate dynamics [13][14][15][16], and how these factors influence yield and yield components. For instance, increased grain yield in response to N application was associated with greater leaf area [9][10][11], ear dry weight (DW) [13][14][15], and developing kernel number per ear [17].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Comparing 0 and 200 kg N ha −1 applied at V6, Rossini et al (2011) reported that biomass allocation to the ear during the CP was not reduced by the lower N rate. In contrast, Peng et al (2016) recently demonstrated increased ear DM 6 d before silking and 8 d after silking with a split application of 300 kg N ha −1 (150 kg ha −1 at planting, 75 kg ha −1 at V6, and 75 kg ha −1 at V10) compared with either 0 or 150 kg N ha −1 applied at planting. Examining N rates of 0 to 180 kg N ha −1 applied either at planting or V6, Uhart and Andrade (1995a) found that AEGR tended to increase with increasing N rate, but the increase in AEGR was proportional to the increase in crop growth rate.…”
Section: Resultsmentioning
confidence: 93%
“…Many studies have shown that the application of nitrogen fertilizer can improve the photosynthetic capacity, nitrogen content, total biomass, and grain yield but decrease the NUE (Peng et al, 2016;Hammad et al, 2017). Similar to previous studies, our results showed that the application of N300 increased the grain yield by 2-15% compared with N150.…”
Section: Discussionmentioning
confidence: 99%